Revision of a nonunited subtrochanteric femoral fracture around a failed intramedullary nail with the use of RIA products, BMP-7 and hydroxyapatite: a case report - Tzioupis, Christopher (BioMed Central, 2011)
INTRODUCTION: Femoral subtrochanteric fractures are commonly treated using intramedullary devices. Failure of the implant and subsequent nonunion is still an issue, however, and limited evidence exists regarding the most appropriate treatment. CASE PRESENTATION: We report the case of an 80-year-old Caucasian woman with a subtrochanteric fracture originally treated using a trochanteric gamma nail which failed, resulting in a nonunion and fracture of its proximal end. The nonunion was revised with the removal of the broken trochanteric gamma nail, application of a condylar blade plate, ipsilateral Reamer/Irrigator/Aspirator autografting, recombinant human bone morphogenetic protein-7 and injectable hydroxyapatite cement. The fracture united fully at ten months following revision surgery, with no signs of femoral head avascular necrosis at 18-month follow-up. CONCLUSION: The essential requirements for success when revising a nonunited fracture are to provide anatomical reduction, mechanical stability, bone defect augmentation and biological stimulation to achieve healing. Current advances in molecular biology, such as recombinant human bone morphogenetic protein-7, and biotechnology such as the Reamer/Irrigator/Aspirator system and hydroxyapatite injectable cement can improve patient outcomes over the use of our traditional revision techniques.